PURIFICATION OF CONSTRUCTION MATERIALS OF SPENT FUEL ASSEMBLIES BY COLD CRUCIBLE INDUCTION MELTING - M. Yu. Kalenova; A. V. Dmitrieva; I. V. Kuznetsov; А. М. Koscheev; O. E. Budin; A. S. Schepin (Тонкие химические технологии)
«New atomic energy technologies» federal program is being realized in Russia. This program includes experimental energy complex development and building, which contains: - a natural safety lead coolant fast reactor «BREST-300»; - a spent fuel recycle facility including fuel fabrication and re-fabrication, radioactive waste immobilization and discarding in accordance with radioactively-equivalent state. The current recycle facility preliminary design involves dry operation of spent fuel elements disassembly using steel shell dissolution by liquid zinc. Fuel element shells are made of special radiation-proof steel «EP-823» containing the following amounts of elements (%): C - 0.2; Мn - 0.8; Si - 1; S - 0.01; Р - 0.015; Сr - 12; Ni - 0.5; Мо - 0.9; V - 0.2; N - 0.05; Fe - 84.325. After dissolution zinc liquid containing steel elements is distilled. Still zinc is sent back to shells dissolution. The bottom product is destructurized particulate with the composition corresponding to original steel. Actinides steel shell and bottom product contamination was predicted using computer modeling. In accordance with the project technical specification actinide content in the disposable materials must be under 0.0001%. Thus, the bottoms product should be purified. Oxidative slag cold crucible induction melting purification was chosen and tested in laboratory scale. The following slag types were investigated: Al2O3-SiO2, B2O3-SiO2, Al2O3 - CaO. It was found that the most appropriate slag is B2O3-SiO2, and the optimal process temperature is about 1600°C.